2016
DOI: 10.1186/s40064-016-2319-x
|View full text |Cite
|
Sign up to set email alerts
|

Oyster crude polysaccharides attenuates lipopolysaccharide-induced cytokines production and PPARγ expression in weanling piglets

Abstract: This study evaluated whether oyster crude polysaccharides (OPS) attenuates lipopolysaccharide (LPS)-induced immune stress in weanling piglets. Thirty healthy crossbred piglets (28 ± 1 days old) were randomly divided into five groups (6 piglets/group). Blank control and LPS groups were fed with the basal diet, while low, medium and high dose of OPS groups were fed with the basal diet supplemented with 0.5, 0.8 and 1.2 % OPS, respectively, for 30 days. LPS group, as well as low, medium and high dose of OPS group… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 32 publications
0
1
0
Order By: Relevance
“…Oligosaccharides and a phenolic antioxidant extracted from Crassostrea gigas exhibit strong antioxidant activities (Watanabe et al., 2012 ; Wu & Huang, 2017 ). Yin et al found that oyster crude polysaccharides (OPS) could attenuate lipopolysaccharide (LPS)‐induced immune stress in weanling piglets (Yin et al., 2016 ). Moreover, another study demonstrated that treatment of human peripheral blood mononuclear cells (PBMCs) with an oyster extract enhanced IL‐2‐dependent T cell proliferation (Achour et al., 1997 ).…”
Section: Discussionmentioning
confidence: 99%
“…Oligosaccharides and a phenolic antioxidant extracted from Crassostrea gigas exhibit strong antioxidant activities (Watanabe et al., 2012 ; Wu & Huang, 2017 ). Yin et al found that oyster crude polysaccharides (OPS) could attenuate lipopolysaccharide (LPS)‐induced immune stress in weanling piglets (Yin et al., 2016 ). Moreover, another study demonstrated that treatment of human peripheral blood mononuclear cells (PBMCs) with an oyster extract enhanced IL‐2‐dependent T cell proliferation (Achour et al., 1997 ).…”
Section: Discussionmentioning
confidence: 99%